PERAN YAYASAN ANAK DAN PEREMPUAN DALAM PEMBERDAYAAN KESEHATAN DAN EKONOMI DI KALANGAN PEKERJA SEKS PEREMPUAN - Defa Tsamara Zafirah; WG Pramita Ratnasari (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2022)
The problems faced by Female Sex Workers (FSWs) are low economic problems, vulnerability to HIV/AIDS or STIs, and not having other decent work options. Yayasan Anak dan Perempuan (YAP) is a foundation that assists FSWs in North Jakarta to change their social, health, and economic conditions. This study aims to describe the roles of YAP, the results of empowerment, and identify inhibiting and supporting factors in the health and economic empowerment among FSWs through the HIV/AIDS Program and the Economic and Education Program. This study used a qualitative research method, purposive sampling technique, data mining through observations, interviews, and literature studies. The results show that YAP plays facilitative roles, educational roles, representational roles, and technical roles in health and economic empowerment among FSWs. The results of empowerment in the fields of education and health are considered optimal, while in the spiritual and economic fields are considered not optimal. Several factors that hindered YAP in empowering PSP are there is no provision of religious education, no further training regarding tips for maintaining and developing a business, etc. Supporting factors, include: mentoring is carried out by staff who have the same experience as FSWs, etc.